2002
DOI: 10.1103/physrevlett.89.237205
|View full text |Cite
|
Sign up to set email alerts
|

Magnetization-Direction-Dependent Local Electronic Structure Probed by Scanning Tunneling Spectroscopy

Abstract: Scanning tunneling spectroscopy (STS) of thin Fe films on W(110) shows that the electronic structure of domains and domain walls is different. This experimental result is explained on the basis of first-principles calculations. A detailed analysis reveals that the spin-orbit induced mixing between minority d xyxz and minority d z 2 spin states depends on the magnetization direction and changes the local density of states in the vacuum detectable by STS. As a consequence nanometer-scale magnetic structure infor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
116
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(118 citation statements)
references
References 18 publications
1
116
1
Order By: Relevance
“…
Understanding the role of spin-orbit coupling (SOC) has been crucial to controlling magnetic anisotropy in magnetic multilayer films [1][2][3][4]. It has been shown that electronic structure can be altered via interface SOC by varying the superlattice structure, resulting in spontaneous magnetization perpendicular or parallel to the plane [5,6].
…”
mentioning
confidence: 99%
“…
Understanding the role of spin-orbit coupling (SOC) has been crucial to controlling magnetic anisotropy in magnetic multilayer films [1][2][3][4]. It has been shown that electronic structure can be altered via interface SOC by varying the superlattice structure, resulting in spontaneous magnetization perpendicular or parallel to the plane [5,6].
…”
mentioning
confidence: 99%
“…Therefore, they do not affect the position or the measured width of magnetic domain walls or magnetic vortices [21]. Moreover, it has been demonstrated that even a non-magnetic probe tip may be able to image domain walls since the local electronic structure is modified within the domain wall due to the local change of the magnetization direction and the accompanied change of the spin-orbit coupling between electronic states [22,23].To summarize this part, SP-STS allows us to enter a new regime of magnetic domain and domain wall observation at sub-nanometer scale spatial resolution which is not accessible by any other magnetic imaging technique up to now. …”
mentioning
confidence: 99%
“…The most likely mechanism for the TAMR is that the s-o interaction causes a mixing of 3d minority and majority spin states, as well as 4s and 3d orbitals of the same spin channel, resulting in an anisotropic tunneling DOS at the Fermi level. 13,14 A detailed theoretical analysis would require spin density functional calculations, which is clearly beyond the scope of the present work. Nevertheless, a qualitative understanding of the large difference in temperature dependence between TMR and TAMR can be gained by considering the magnetocrystalline anisotropy.…”
mentioning
confidence: 99%